2015
DOI: 10.1093/brain/awv360
|View full text |Cite
|
Sign up to set email alerts
|

Enhanced phasic GABA inhibition during the repair phase of stroke: a novel therapeutic target

Abstract: While tonic GABA appears to suppress brain repair after stroke, the effects of phasic (synaptic) GABA signalling are unclear. Hiu et al. reveal an increase in phasic GABA signalling during the repair phase that enhances plasticity-related recovery in mice. Increasing phasic signalling with zolpidem improves behavioural recovery, suggesting therapeutic potential.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
79
1

Year Published

2016
2016
2021
2021

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 100 publications
(85 citation statements)
references
References 53 publications
5
79
1
Order By: Relevance
“…25 Furthermore, altered tonic and phasic GABA (gamma aminobutyric acid) (Cl − ) signaling has been reported to occur after stroke, and targeted treatments provide behavioral benefit. 26,27 Taken together, these findings indicate that ion homeostasis is impaired after nervous system injury with functional consequences, and therapies that normalize ion concentration or signaling, including rehabilitation, can be beneficial. However, it should be noted that beginning such treatments soon after stroke can be harmful (eg, increased lesion size).…”
Section: Discussionmentioning
confidence: 91%
“…25 Furthermore, altered tonic and phasic GABA (gamma aminobutyric acid) (Cl − ) signaling has been reported to occur after stroke, and targeted treatments provide behavioral benefit. 26,27 Taken together, these findings indicate that ion homeostasis is impaired after nervous system injury with functional consequences, and therapies that normalize ion concentration or signaling, including rehabilitation, can be beneficial. However, it should be noted that beginning such treatments soon after stroke can be harmful (eg, increased lesion size).…”
Section: Discussionmentioning
confidence: 91%
“…Interestingly, while tonic GABA signaling is increased after stroke, phasic GABA signaling mediated via synaptic GABA-A receptors is decreased after stroke. Recently our group demonstrated that enhancing phasic GABA signaling promotes post-stroke recovery, further highlighting the importance of phasic GABA signaling in recovery [157]. The GABA-B receptor may also play an important role in stroke recovery, as these receptors are thought to mediate interhemispheric inhibition [158].…”
Section: Optogenetic Interrogation Of Post-stroke Remapping and Recoverymentioning
confidence: 97%
“…ATD uses a combination of physical sectioning and deconvolved wide-field imaging to generate an unparalleled combination of acquisition speed, volumetric resolution (100 nm by 100 nm by 50–70 nm) and molecular multiplexing (Wang and Smith, 2012; Micheva and Smith, 2007). Using ATD, different populations of synapses can be classified from large regions of the cortex based on molecular markers (Wang et al, 2014; Micheva et al, 2010; Allen et al, 2012; Hiu et al., 2016). These EM verified algorithms can be used to extract different classes of synapses (excitatory, inhibitory and their subclasses) at large numbers (>1 million) with low error rates (false positive 5%, false negative 12% – for more on antibody verification and error rates see 'Methods') (Wang et al, 2014; Allen et al, 2012; Hiu et al, 2016).…”
Section: Introductionmentioning
confidence: 99%
“…Using ATD, different populations of synapses can be classified from large regions of the cortex based on molecular markers (Wang et al, 2014; Micheva et al, 2010; Allen et al, 2012; Hiu et al., 2016). These EM verified algorithms can be used to extract different classes of synapses (excitatory, inhibitory and their subclasses) at large numbers (>1 million) with low error rates (false positive 5%, false negative 12% – for more on antibody verification and error rates see 'Methods') (Wang et al, 2014; Allen et al, 2012; Hiu et al, 2016). Moreover, these algorithms return the molecular features of each synapse organized around a spatial vector that defines the presynaptic bouton to post-synaptic density (Wang et al, 2014; Allen et al, 2012; Hiu et al, 2016) (see Figure 1E).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation